New Tools in Social Practice: Learning, Medical Education and 3D Environments - Ludvigsen, Sten; Fjuk, Annita (Outlines. Critical Practice Studies, 2001)
Learning with different kinds of ICT-based tools is an important issue in today’s society. In this article we focus on how design of technology rich environments based on state of the art learning principles can give us new insights about how learning occur, and how we can develop new types of learning environments. Medical education constitutes the subject domain. There has been a considerable effort to develop 3D technologies in this field, and the article provides a careful review of how these technologies are applied. There is, however, a substantial gap between these advances and the use of technologies in medical education. Related work proposes individualistic assumptions or metaphors that do not focus explicitly on learning and technology mediation. Based on theoretical analysis of previous literature in the field we argue that there is a need for a new unit of analysis that includes the relationship between individual and collective activity and the role of technology herein. The socio-cultural and especially activity theory is taken as the perspective which gives the possibility to develop the argumentation about the unit of analysis. The unit of analysis also has implications for design of 3D environments. The design principles are elaborated upon and examples are given in relation to an application called Matador (Medical Advanced Training in an Artificial Distributed Environment). Matador is aimed at developing a simulation environment for training in emergency medicine.